IMPLEMENTASI KURIKULUM 2013 DALAM PENDIDIKAN INKLUSI DI ROYAL WELLS SCHOOL KOTA BEKASI - YUDHA HADI PURNAMA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2021)
The curriculum in inclusive classes must be developed by following the needs and conditions of each student. The curriculum used is a modified curriculum as well as the embodiment of a child-friendly school. This study aims to look at the implementation of the curriculum in inclusive education providers related to aspects of planning, implementation and evaluation of learning as well as the supporting and inhibiting factors for the implementation of inclusive education. This research was conducted using a descriptive method, and a qualitative approach was carried out at the Royal Wells School in Bekasi City. Data mining used interview, observation and document study techniques. The results of the study indicate that schools are required to carry out curriculum alignment by conducting assessments-developing individual learning programs-discussions with parents, class teachers, and school principals. In the implementation of classroom learning carried out by class teachers, but for Inclusive Students who receive material during learning are guided by special assistant teachers. And for the evaluation of learning, it is done by adjusting the level of difficulty of the questions, the number of questions, and how to answer questions that are adjusted to the abilities of students. To achieve this goal, support from leaders, peers and parents of students is very much needed, while several inhibiting factors are that there are still policies at the school level that are not yet comprehensive, people who do not understand, planning for curriculum alignment that has not been supervised, inadequate facilities and infrastructure. adequate. The recommendation from the results of this study is that the school must disseminate policies to prospective parents of students both regularly and inclusively, pay attention to the competence of teaching staff resources, and supervise the implementation of inclusive education in schools. ABSTRAKKurikulum pada kelas inklusi harus dikembangkan dengan mengikuti kebutuhan dan kondisi masing-masing siswa. Kurikulum yang digunakan adalah kurikulum modifikasi dan juga sebagai perwujudan sekolah ramah anak. Penelitian ini bertujuan untuk melihat implementasi kurikulum pada sekolah penyelenggara pendidikan inklusif terkait aspek perencanaan, pelaksanaan dan evaluasi pembelajaran serta faktor pendukung dan penghambat penyelenggaraan pendidikan inklusif. Penelitian ini dilakukan dengan menggunakan metode deskriptif, dan pendekatan kualitatif yang dilakukan di Sekolah Royal Wells School di Kota Bekasi. Penggalian data menggunakan teknik wawancara, observasi dan studi dokumen. Hasil penelitian menunjukkan bahwa sekolah wajib melakukan penyelarasan kurikulum dengan cara melakukan asesmen-mengembangkan program pembelajaran individual-diskusi dengan orang tua, guru kelas, dan kepala sekolah. Pada pelaksanaan pembelajaran di kelas yang dilakukan oleh guru kelas, namun bagi Siswa Inklusiyang menerima materi saat pembelajaran dibimbing oleh guru pendamping khusus. Dan untuk evaluasi pembelajaran dilakukan dengan penyesuaian tingkat kesulitan pertanyaan, jumlah soal, dan cara menjawab pertanyaan yang disesuaikan dengan kemampuan peserta didik. Untuk mencapai tujuan tersebut dukungan pimpinan, rekan sejawat dan orang tua murid sangat dibutuhkan, sedangkan beberapa faktor yang menghambat adalah masih terdapat kebijakan di tingkat sekolah yang belum komprehensif, masyarakat yang belum paham, perencanaan penyelarasan kurikulum yang belum di supervisi, sarana dan prasarana yang kurang memadai. Rekomendasi dari hasil penelitian ini adalah sekolah tersebut harus melakukan sosialisasi kebijakan kepada calon orangtua siswa baik regular maupun inklusif, memperhatikan kompetensi sumber daya tenaga pengajar, serta melakukan supervisi implementasi pendidikan inklusif di sekolah.